Motivasi Petani Mempertahankan Lahan Sawah dari Alih Fungsi Lahan (Kasus Subak Tengaling, di Desa Pejeng, Kecamatan Tampaksiring, Kabupaten Gianyar) (Jurnal Agribisnis dan Agrowisata, 2025)
The Motivation of Farmers to Defend Paddy Fields from Land Conversion (The Case of Subak Tengaling, Pejeng Village, Tampaksiring District, Gianyar Regency). The agricultural sector is a sector that plays a big role in terms of food availability and suitability. However, population growth and development dynamics have shifted land use which eventually poses problems. Changes in the use of agricultural land to non-agricultural can also be referred to as land conversion. Land function change or commonly referred to as land function change is a change in the function of part or all of the land area from its original function (according to plan) to other functions that have a negative impact (problem) on the environment and the potential of the land itself. Bali itself, it is not spared from the impact of land conversion. This can be seen from year to year the land area in Bali continues to decline, this is due to the rapid growth of the tourism sector in Bali. Gianyar Regency is one of the regions in Bali Province whose tourism development is very rapid, one of which is Ubud District, Gianyar Regency which is a tourism center area that causes the surrounding area to be affected by land conversion. Pejeng Village, which is one of the villages in Tampaksiring District, Gianyar Regency, is affected by the rapid development of tourism in Gianyar Regency. The location of Pejeng Village, which is the border between tourism centers in Ubud, has caused many investors to hunt for productive land in this area. What is interesting here is that farmers continue to maintain their land, so it is interesting to conduct research on the motivation of farmers to defend their fields from land conversion in Pejeng Village, Tampaksiring District, Gianyar Regency.
Keywords: motivation; land conversion; tourism